The Effects of a Multidimensional Exercise Program on Health Behavior and Biopsychological Factors in Mexican Older Adults - Borbón-Castro, Norma Angélica; Castro-Zamora, Andrés Aquilino; Cruz-Castruita, Rosa María; Banda-Sauceda, Nancy Cristina; De La Cruz-Ortega, Manuel Francisco (Frontiers in Psychology, 2020)
Background: The population of older adults is increasing worldwide which brings attention to the importance of healthy aging. Adopotion of healthy lifestyle activities such as participating in physical activity on a daily basis is key to maintaining physical and mental health. The aim of this study was to investigate the effects of participation in a 12-week multidimensional exercise program on health behavior and biopsychosocial factors of older adults living in Northeastern Mexico. Methods: A quasi-experimental study was conducted with 45 older adults (35 females and 10 males; M = 67.24 ± 5.73 years). The participants were assigned to an experimental group (n = 23) that participated in a 12-week exercise program and a control group (n = 22). Pre- and post-analyses of the exercise intervention data were carried out to investigate the participants’ health-related variables including physical activity levels, blood pressure, self-esteem, depressive symptoms, and blood lipids profiles. Results: The results indicated that the exercise intervention contributed to significant improvements in the older adults’ health-related variables for the experimental group (EG) when contrasted with the control group. For instance, the EG significantly improved systolic (p < 0.001) and diastolic (p < 0.027) blood pressure, blood lipids (e.g., cholesterol (p <0.05), triglycerides (p <0.05), self-esteem (p < 0.005), and depressive symptoms (p < 0.002) as well as physical activity levels (p < 0.001). The results also demonstrated that only those individuals in the EG diagnosed with disease benefited from improved self-esteem and physical activity levels when contrasted with their healthy counterparts.